2016
DOI: 10.1016/j.engstruct.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optimal designs of steel portal frames including topological asymmetry considering rolled, fabricated and tapered sections

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. AbstractA structural design optimisation has been carried out to allow for asymmetry and fully tapered portal frames. The additional weight of an asymmetric structural shape was found to be on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Despite a greenhouse structure requires a 3D definition to include the influence of the external loads as well as the effect of the structural elements responsible for the connections (i.e., purlins and gutters), Briassoulis et al [33] demonstrated that the study of the main planes (two-dimensional (2D) analysis) was a valid approach in the assessment of greenhouses. In fact, such simplification has been commonly employed in both industrial and agricultural constructions [59][60][61][62][63]. In the same way, Ren et al [47] also performed a similar simplification by means of 3D models in order to decrease the computational cost.…”
Section: Geometrymentioning
confidence: 99%
“…Despite a greenhouse structure requires a 3D definition to include the influence of the external loads as well as the effect of the structural elements responsible for the connections (i.e., purlins and gutters), Briassoulis et al [33] demonstrated that the study of the main planes (two-dimensional (2D) analysis) was a valid approach in the assessment of greenhouses. In fact, such simplification has been commonly employed in both industrial and agricultural constructions [59][60][61][62][63]. In the same way, Ren et al [47] also performed a similar simplification by means of 3D models in order to decrease the computational cost.…”
Section: Geometrymentioning
confidence: 99%
“…In terms of optimisation at the frame level, most of the previous studies have been conducted for portal frames composed of hot-rolled steel sections (e.g. (McKinstray et al, 2015, McKinstray et al, 2016). As a rare exception, Phan et al (2019) developed a coupled element and structural level optimisation framework to improve the structural performance of CFS portal frames at the serviceability and ultimate limit states.…”
Section: Introductionmentioning
confidence: 99%
“…McKinstray et al [21] optimally designed the single-span industrial steel frames. In which three types of sections (rolled, fabricated and non-prismatic) were used in the frames.…”
Section: Introductionmentioning
confidence: 99%